The Effect of the Educational Intervention Based on the Theory of Protection Motivation in Preventing Cutaneous Leishmaniasis - Elham Charoghchian Khorasani; Mahmood Fakhar; Atiye Kamel Khodabande; Nooshin Peyman (Gonabad University of Medical Sciences, 2024)
Background: Cutaneous leishmaniasis is one of the most common diseases in Iran. This research was conducted to determine the effect of the educational intervention based on the theory of conservation motivation on the prevention of cutaneous leishmaniasis in boys in the seventh, eighth, and ninth grades in the population covered by Mashhad Health Center No. 1, Mashhad City, Iran, in 2020. Methods: In this quasi-experimental study, 80 (out of the 23152) seventh, eighth, or ninth grade students covered by Mashhad Health Center No. 1 were selected by random cluster sampling. After determining the needs in the framework of the protection motivation theory, an educational intervention was designed and implemented for the experimental group. Two groups completed study questionnaires before, immediately after, and three months after the educational intervention. Finally, the obtained data were analyzed using Mann-Whitney, chi-square, and Fisher exact tests in SPSS software, version 24. Results: Before the intervention, the two groups showed no significant differences regarding the theoretical structure of conservation motivation. After the intervention in the experimental group immediately after and three months after the intervention, significant differences were observed regarding the mean scores of the perceived sensitivity (P>0.001), perceived intensity (P>0.001), fear (P>0.001), perceived response effectiveness (P>0.001), protection motivation (P>0.001) and behavior (P>0.001) of the cutaneous leishmaniasis. In the control group, the changes were not significant. Conclusion: The educative intervention based on motivational protection theory in male adolescents has a significant increase in the preventative behaviors of cutaneous leishmaniasis, and the protection motivation theory can be used as a framework in designing educational programs to promote the preventive behaviors of cutaneous leishmaniasis in male adolescents.